Annals Graphic Medicine - Dear Doctor II - Councilor, KC (Annals of Internal Medicine, 2017)
Keywords: dept.com

Annals Graphic Medicine - Dear Doctor I - Councilor, KC (Annals of Internal Medicine, 2017)
Keywords: dept.com

Is it safe to bring myself to work? Understanding LGBTQ experiences of workplace dignity - Baker, Sara J; Lucas, Kristen (Canadian Journal of Administrative Sciences-revue Canadienne Des Sciences De L Administration, 2017)
Despite increased efforts by more organizations to be seen as “gay-friendly,” workplaces remain challenging sites for LGBTQ employees to navigate. We examine the ways in which LGBTQ employees experience dignity threats in the workplace and the protection strategies they use to deflect those threats. Interviews with 36 LGBTQ working adults revealed that their dignity is threatened by a range of identity-sensitive inequalities that undermine their safety and security when they claim authentic gendered/sexual identities. Specific safety and security threats to dignity include social harm, autonomy violations, career harm, and physical harm. To (re)claim their dignity, they engage in four primary dignity protection strategies: avoiding harm by seeking safe spaces, deflecting harm with sexual identity management, offsetting identity devaluations by emphasizing instrumental value, and creating safe spaces for authenticity and dignity. Copyright (C) 2017 ASAC. Published by John Wiley & Sons, Ltd.
Keywords: authenticity; dept.com; gay-friendly; heteronormativity; safety; sexual identity management; workplace dignity